TECHNICAL, ENVIRONMENTAL, AND ECONOMIC ASSESSMENT OF SLUDGE THICKENING PROCESSES: A COMPARISON OF CONVENTIONAL THICKENING AND ENERGY-EFFICIENT CENTRIFUGAL THICKENING TECHNOLOGIES - Gable, Joshua J. (My University, 2014)
As of today, several technologies are available for thickening waste activated sludge. Presently gravity belt thickeners (GBTs) tend to be the most commonly installed for waste activated sludge thickening applications (Water Environment Federation, 2012). However, new advancements in thickening centrifuges give reason to believe that the centrifuge may be economically competitive with GBTs and other thickening technologies moving forward, creating a need to compare the economic favorability of each process. In addition, little research has presently been completed in assessing the environmental impact of thickening technologies. Thus, the objective of this study was to compare GBTs with a novel centrifugal thickening technology and compare them on the basis of performance, economy, and environmental impact. GBTs were found to utilize less power than the centrifugal thickener however reduction in the amount of polymer consumed gave a large advantage to the centrifugal thickening technology over the GBT, specifically for larger sized plants.
Keywords: biosolids; gravity belt thickeners; THK; centrifuge; thickening; Waste activated sludge